Pengaruh Job Stres dan Job Satisfaction terhadap Psychological Well-Being - Fellia Sakti Dewi Washinta; Hafid Kholidi Hadi (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study aims to analyze the effect of job stress and job satisfaction on the psychological well-being of postgraduate employees at the State Islamic University of Sunan Ampel Surabaya. This research method uses quantitative research, with the method used in sampling is saturated sampling. The population used is 41 employees. The analysis of this study using Multiple Linear Regression Analysis by IBM SPSS Statistics 24.0 software. This study concluded that job stress has a negative and meaningful effect on psychological well-being because the burden of many tasks results in stress that causes psychological well-being to decrease. For job satisfaction has a positive and meaningful effect on psychological well-being, the lack of employees results in dissatisfaction when doing work that affects psychological well-being. Meanwhile, the meaningful effect of job stress and job satisfaction on psychological well-being occurs because the simultaneous significance test (f test) are overall Ho is accepted. Institutions must pay attention to work stress experienced by their employees so that the psychological well-being of employees can be well maintained and will have a good impact on employee job satisfaction.